2022
DOI: 10.1021/acs.biochem.2c00505
|View full text |Cite
|
Sign up to set email alerts
|

Engineered RecA Constructs Reveal the Minimal SOS Activation Complex

Abstract: The SOS response is a bacterial DNA damage response pathway that has been heavily implicated in bacteria’s ability to evolve resistance to antibiotics. Activation of the SOS response is dependent on the interaction between two bacterial proteins, RecA and LexA. RecA acts as a DNA damage sensor by forming lengthy oligomeric filaments (RecA*) along single-stranded DNA (ssDNA) in an ATP-dependent manner. RecA* can then bind to LexA, the repressor of SOS response genes, triggering LexA degradation and leading to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 79 publications
4
12
0
Order By: Relevance
“…Despite it might be affected by the oligonucleotide length used in the assay, the affinity of RecAPa towards ssDNA is in the expected range. The binding constant between the components of the activation complex results in a remarkable agreement with the previously determined one for a full-length E. coli LexA S119A with its cognate RecA* (360 nM; Cory et al, 2022). Our experimental data strongly supports the most accepted model proposed for the activation of the SOS response (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite it might be affected by the oligonucleotide length used in the assay, the affinity of RecAPa towards ssDNA is in the expected range. The binding constant between the components of the activation complex results in a remarkable agreement with the previously determined one for a full-length E. coli LexA S119A with its cognate RecA* (360 nM; Cory et al, 2022). Our experimental data strongly supports the most accepted model proposed for the activation of the SOS response (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Fluorescence polarization-based studies Fluorescence polarization (FP) was used as the biophysical readout to observe and quantify the binding of RecAPa to ssDNA and LexAPa to RecAPa*. To determine the apparent affinity of RecAPa for ssDNA and ATPγS, a 5'-Carboxyfluoresceinated 32mer oligonucleotide (FAM-32mer; Supplementary Table 3) was used as "scaffold" (Lee et al, 2007;Cory et al, 2022). In the former experiment, 10 nM FAM-32mer ssDNA was incubated with different concentrations of RecAPa and an excess of ATPγS (1 mM) for 30 min at 37 °C before reading the FP signal.…”
Section: Model Building Refinement and Structural Analysismentioning
confidence: 99%
“…Despite decades of study, the absence of insight into the structural underpinnings of SOS complex formation has been one limitation to the rational design of small-molecule SOS antagonists. While the structures of RecA* and LexA have been solved separately, these efforts have led to vastly different models of complex formation, as evidenced by the suggestion that anywhere from three to seven RecA monomers might be involved in the protein interface [41][42][43][44] . Prior low-resolution negative stain electron microscopy studies helped to identify that LexA binds in the helical groove of the RecA* filament 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploiting the properties of Acd for FP enhanced our understanding of the kinetics of SOS complex assembly and offered some limited insights into LexA orientation relative to RecA*. In a subsequent study, we used the same FP assay in combination with genetic fusion of RecA monomers, forming concatenated multimers of 2–6 RecA subunits (Cory et al, 2022b). Measuring binding of LexA using Acd FP as well as other assays, we determined that three RecA subunits are sufficient to activate LexA.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a 13mer ssDNA is expected to bind 4 RecA subunits (Rajan et al, 2006), limiting the assembled complex to a single LexA binding site as determined in our FP experiments described above (Figure 8). Although we have shown that it is possible for LexA to bind to filaments of only three RecA subunits, the affinity of ssDNA for the RecA 3mer is 5-fold lower compared to the RecA 4mer (Cory et al, 2022b). Therefore, we designed our experiments to target a RecA 4mer using the 13mer ssDNA in order to maximize formation of the ternary SOS complex, as discussed in more detail below.…”
Section: Sos Complex Acd Fretmentioning
confidence: 99%